О возможности применения микроконтроллеров для on-line оценки погрешности дистанционного измерения температуры воздуха - Ибраимов, И. К. (ХНУРЕ, 2020)
To assess the possibility of using microcontrollers for on-line evaluation of the error of remote measurement of air temperature, it is necessary to assess the complexity of the required algorithm and software. Errors of radio-acoustic temperature measurement are divided into 2 types of hardware and geophysical. The results of calculating the error in determining the temperature depending on the error in determining c and setting the sensing directions are presented. For the correct calculation of this correction, it is necessary to take into account the actual spatial distribution of the phases and amplitudes of the radio and sound radiation. Such experiments were not performed. Assessment of the complexity of the algorithm can be carried out on the basis of theoretical analysis.
Keywords: микроконтроллер; on-line оценка; дистанционное измерение температуры воздуха